2022
DOI: 10.3390/genes13122346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of BglI rs739837 and TaqI rs731236 Polymorphisms in Vitamin D Receptor with SARS-CoV-2 Variants Mortality Rate

Abstract: A lack of vitamin D is a potential risk factor for coronavirus disease (COVID-19). Variants in the Vitamin D Receptor (VDR) gene, such as BglI rs739837 and TaqI rs731236, are associated with various viral infection progressions. This study aimed to evaluate the relationship between the BglI rs739837 and TaqI rs731236 polymorphisms and the mortality rate of COVID-19 based on severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) variants. The genotyping of BglI rs739837 and TaqI rs731236 genotypes was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Nevertheless, to the best of our knowledge, this is the first case-control study evaluating the association between VDR polymorphisms and severity of COVID-19 in the Greek population. Our findings are in line with other studies showing a positive association of the TaqI C allele with COVID-19 morbidity [ 16 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, to the best of our knowledge, this is the first case-control study evaluating the association between VDR polymorphisms and severity of COVID-19 in the Greek population. Our findings are in line with other studies showing a positive association of the TaqI C allele with COVID-19 morbidity [ 16 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…The TaqI variant allele and the FF variant FokI genotype can alter response to vitamin D supplementation and are associated with a better response (Usategui-Martín et al 2022 ). Other researchers indicated that the mortality rate or severity of SARS-CoV-2 with different variants was associated with a low level of 25-OHD and that VDR SNPs regulate susceptibility to infection with COVID-19 (Camporesi et al 2022 ; Al-Gharawi et al 2023 ; Albu-Mohammed et al 2022 ; Protas et al 2023 ). Furthermore, it has been shown that patients with FokI and TaqI gene polymorphisms may be at higher risk of COVID-19 pandemic infection, and VD supplementation is recommended for individuals in the period surrounding or after the COVID-19 pandemic (Mamurova et al 2023 ; Zeidan et al 2023 ; Shawi et al 2023 ) .…”
Section: Genetic Polymorphisms Of the Vitamin D Could Explain The Con...mentioning
confidence: 99%
“…Another Iranian study analyzed two VDR genetic variants [rs739837 (BglI) and rs731236 (TaqI)] in patients infected with alpha, delta or omicron variants of SARS-CoV-2 virus. Their results suggested that genetic variants may be either protective or risk factors in COVID-19 depending on the virus strain [41]. Yet another study from Iran enrolled 500 patients with COVID-19 (160 asymptomatic, 250 mild/moderate, and 90 severe/critical cases) to analyze eight variants in VDR gene as risk factors of severe COVID-19.…”
Section: Evidence From Nutrigenetic Studies Of Micronutrients In Coro...mentioning
confidence: 99%